YU. V. OPANASENKO: VALERIY KYKOT’S TRANSLATION STRATEGY - OPANASENKO, YU. V. (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Summary. Introduction. The article deals with the translation strategy of a well-known Ukrainian translator, writer, poet and researcher Valeriy Kykot. The topicality of the paper is confined to the insufficient study of the problem of translation strategy taken as a whole as well as of the strategy of individual translators in particular. Purpose. The present article aims to investigate the essence and specifics of Valeriy Kykot’s translation strategy. Methods. The multi-faceted nature of translation strategy, being a complex phenomenon that includes a vast amount of linguistic and extra linguistic realizations, has determined it necessary to employ translatological method being a complex of methods and techniques of analysis. Results. The present paper focuses on the analysis of numerous translations of American poetry by V. Kykot as well as his significant achievements in the field of translation studies. Specifically, he is the translator of verses by more than thirty American poets. These translations have been published in literary and art periodicals, parts of books, as well as in three separate books. V. Kykot’s works in the field of translation studies include candidate’s and doctoral dissertations dealing with poetical translation, a scientific monograph and numerous publications in scientific periodicals in Ukraine and abroad. The essence of V. Kykot’s translation strategy is illustrated by his translation of E. Poe’s verse “Eldorado”. In addition to the comparison of the original poem and its translation by V. Kykot, the author of the article cites other Ukrainian versions of E. Poe’s verse «Eldorado». Originality. The originality of the research is seen in the fact that the present article is the first attempt to investigate Valeriy Kykot’s translation strategy. At the same time it should be pointed out that there have been a number of literary articles and literature reviews on his poetry. Conclusion. Valeriy Kykot is not only a well-known translator, but also a talented poet and a renowned researcher. All these three incarnations have shaped his translation strategy and individual style: as a poet he knows how to create poetry, as a researcher he is familiar with the specifics of literary translation, poetical translation in particular, and as a translator he is able to combine his knowledge from both of the mentioned fields in order to provide high-quality translations of poetry. At the core of V. Kykot’s translation strategy consists in a careful selection of the material to be translated, a thorough analysis not only of the poem itself, but of the personality of its author and the epoch in which he lived and created as well, the identification of the image dominant of each poem and its rendering in translation.